2022
DOI: 10.3390/medicina58081014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Effectiveness of Extracorporeal Shockwave Therapy in Patients with Myofascial Pain or Fibromyalgia: A Scoping Review

Abstract: Myofascial pain syndrome (MPS) and fibromyalgia (FM) are underestimated painful musculoskeletal conditions that could impact function and quality of life. A consensus about the most appropriate therapeutic approach is still not reached. Considering the long course of the diseases, prolonged assumption of drugs, such as NSAIDs and pain killers, could increase the risk of adverse events, often leading affected patients and physicians to prefer non-pharmacological approaches. Among these, radial and focused extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The findings of this pilot RCT suggested that rESWT combined with physical therapy could be effective in relieving pain and improving function in muscle-related TMD patients [ 94 ]. There was another interesting discovery from a qualitative analysis in 2022, which concluded that ESWT could facilitate both clinical and functional recovery in people with myofascial pain syndrome, but not for fibromyalgia [ 95 ]. Another point to note is that extracorporeal radial shockwave therapy combined with ultrasound-guided injection of lidocaine into MTrPs has been shown to be more effective for reducing pain and elastic stiffness in myofascial pain syndrome in the fourth week [ 96 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…The findings of this pilot RCT suggested that rESWT combined with physical therapy could be effective in relieving pain and improving function in muscle-related TMD patients [ 94 ]. There was another interesting discovery from a qualitative analysis in 2022, which concluded that ESWT could facilitate both clinical and functional recovery in people with myofascial pain syndrome, but not for fibromyalgia [ 95 ]. Another point to note is that extracorporeal radial shockwave therapy combined with ultrasound-guided injection of lidocaine into MTrPs has been shown to be more effective for reducing pain and elastic stiffness in myofascial pain syndrome in the fourth week [ 96 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…An additional therapeutic alternative is acupuncture; in the scientific literature many authors have highlighted the effectiveness of this treatment in patients with myofascial pain syndrome ( 43 , 44 ). Several studies have been performed comparing ESWT with other treatment options: Paoletta et al ( 45 ) performed a review on PubMed to analyze the efficacy of ESWT in patients with myofascial syndrome and found a beneficial role of ESWT in improving clinical and functional outcomes; Yalçın et al ( 46 ) compared the efficacy of kinesiotaping (KT) and ESWT on pain threshold and particularly on coordinated movements by neck muscles and concluded that the combination of exercise, KT and ESWT in MPS was effective in all parameters examined. Nahomi Kuroda et al ( 47 ) also conducted a study comparing “ischemic compressions” (IC) with ESWT demonstrating the effectiveness of ESWT in reducing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 36 The fascia is the material basis for MPS to produce pain, and the commonly used treatment methods are mostly acting on the fascia. 37 Therefore, MPS may define the relationship between fascia and pain, and to explore the more scientific definition of MPS is closely related to the relationship between fascia and pain. The prevalence of MPS in clinic due to pain can reach 30% to 93%, 38 and patients and doctors often overlook the importance of MPS as a disease.…”
Section: Discussionmentioning
confidence: 99%